WORSENING OF EXISTING CRANIAL DIABETES INSIPIDUS SYMPTOMS AFTER COMMENCEMENT OF HYDROCORTISONE - RAS, Raja Azafirah; MA, Masliza Hanuni; WA, Siti Sanaa (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Central diabetes insipidus (DI) is a condition that causes persistent thirst and frequent urination. It can develop when a pituitary tumour compresses on the posterior pituitary gland and impairs the gland’s ability to secrete vasopressin hormone. CASE We report a case of a 22-year-old male who presented with a 5-month history of delayed responses, progressive visual loss and lethargy. He also complained of excessive thirst, frequent urination and increased urine volume which was diluted. Clinically, he was dehydrated. Ophthalmological assessment revealed monocular blindness. Computed tomography of the brain reported a suprasellar mass with obstructive hydrocephalus. Anterior pituitary hormone profile revealed panhypopituitarism and laboratory results confirmed the presence of DI. He was managed with hydrocortisone tablets and BD dosing of desmopressin. Unfortunately, he developed episodes of worsening polyuria, and his sodium increased from 143 to 150 mmol 24 hours following commencement of hydrocortisone. His urine output improved following an increment of desmopressin to TDS dosing and his serum sodium normalized. Anterior pituitary hormone profiles showed panhypopituitarism with stalk effect; TSH: 1.192 m IU/L, FT4: 3.9 pmol/L, LH: 0.35 IU/L, FSH: 0.61 IU/L, testosterone: <0.35 nmol/l, ACTH: <0.22 pmol/L, morning cortisol: 108 nmol/L and serum prolactin: 2042 m IU/L. His urine sodium: 47 mmol/L, serum osmolality: 345 mosm/kg, and urine osmolality: 277 mOsm/kg. Pituitary MRI showed a welldefined lobulated suprasellar cystic lesion measuring 2.4 x 2.3 x 1.7 cm, causing compression to the floor of the 3rd ventricle which leads to obstructive hydrocephalus. There was a focally enhancing lesion at the pineal gland. He subsequently underwent a right ventriculoperitoneal shunt and supraorbital craniotomy and biopsy. HPE was reported as germinoma. He is currently stable on hydrocortisone, thyroxine and sublingual desmopressin replacement. CONCLUSION Glucocorticoid replacement may precipitate diabetes insipidus in the setting of adrenal insufficiency. Low cortisol levels will stimulate the release of antidiuretic hormone and increase water reabsorption in the kidney. This effect can be inhibited by exogenous steroids which may then rapidly unmask or worsen central DI.